A new concept for tuning design weights in survey sampling : jackknifing in theory and practice - Singh, Sarjinder, 1963-; Sedory, Stephen; Rueda, Maria; Arcos, Antonio; Arnab, Raghunath (Amsterdam : Academic Press, 2015)
A New Concept for Tuning Design Weights in Survey Sampling: Jackknifing in Theory and Practice introduces the new concept of tuning design weights in survey sampling by presenting three concepts: calibration, jackknifing, and imputing where needed. This new methodology allows survey statisticians to develop statistical software for analyzing data in a more precisely and friendly way than with existing techniques.
4.6. Alternative tuning with a dell function4.6.1. Estimation of variance and coverage; 4.6.2. R code; 4.6.3. Numerical illustration; 4.6.4. R code used for illustration; 4.7. Exercises; Chapter 5: Tuned estimators of correlation coefficient; 5.1. Introduction; 5.2. Correlation coefficient; 5.3. Tuned estimator of correlation coefficient; 5.3.1. Estimation of variance of the estimator of correlation coefficient and coverage; 5.3.2. R code; 5.3.3. Numerical illustration; 5.3.4. R code used for illustration; 5.4. Exercises; Chapter 6: Tuning of multicharacter survey estimators.
CIP data; item not viewed.
Includes bibliographical references and indexes.
Keywords: Sampling (Statistics); Sampling (Statistics); Sampling (Statistics); Mathematics -- Probability & Statistics -- General; Electronic books; Electronic books